2011
DOI: 10.1002/hyp.8106
|View full text |Cite
|
Sign up to set email alerts
|

Continuous measurement of spectrophotometric absorbance in peatland streamwater in northern England: implications for understanding fluvial carbon fluxes

Abstract: Bog systems tend to have a flashy hydrological regime with low baseflows and rapid and high storm peaks. Water derived from peatlands often contains significant amounts of organic humic and fulvic materials which largely form the dissolved organic carbon fraction of the fluvial carbon flux. However, most estimates of dissolved organic flux from peatlands are based on sampling that is infrequent and which may miss the periods of high flux during storm events. In order to better characterise the behaviour and fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 54 publications
2
37
0
Order By: Relevance
“…Consequently, CO 2 fluxes and [DOC] showed strong seasonality: the lowest CO 2 fluxes were observed during the winter months, when low temperatures suppressed photosynthesis and decomposition processes, and the highest fluxes occurred during summer, when biological processes were promoted by warmer temperatures (Clark and others 2005;Bonnett and others 2006). Pore water [DOC] did not peak until autumn, attributable to the relatively high temperatures in summer and autumn that promoted decomposition and mobilization into the dissolved phase in autumn when the water table rose (Tables 4, 5) (Grayson and Holden 2012). CH 4 also peaked in autumn, which coincided with relatively high water tables and temperature (including at depth) (Tables 4, 5).…”
Section: The Importance Of Season Pft and The Integrated Effect Of mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, CO 2 fluxes and [DOC] showed strong seasonality: the lowest CO 2 fluxes were observed during the winter months, when low temperatures suppressed photosynthesis and decomposition processes, and the highest fluxes occurred during summer, when biological processes were promoted by warmer temperatures (Clark and others 2005;Bonnett and others 2006). Pore water [DOC] did not peak until autumn, attributable to the relatively high temperatures in summer and autumn that promoted decomposition and mobilization into the dissolved phase in autumn when the water table rose (Tables 4, 5) (Grayson and Holden 2012). CH 4 also peaked in autumn, which coincided with relatively high water tables and temperature (including at depth) (Tables 4, 5).…”
Section: The Importance Of Season Pft and The Integrated Effect Of mentioning
confidence: 99%
“…In northern latitudes, there are strong seasonal controls over GHG exchange and [DOC]: warmer temperatures generally enhance C cycling in summer (Ward and others 2007;Clark and others 2008) while seasonally lower water tables decrease photosynthesis rates and net CH 4 emissions, and increase respiration and DOC production (Blodau and others 2004). However, increases in DOC production may not be apparent in pore and stream water DOC samples until autumn when the water table commonly rises causing an 'autumn flush' of DOC produced over the summer (Grayson and Holden 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several studies (Aubert and Breuer, 2016;Avagyan et al, 2014;Grayson and Holden, 2012;Huebsch et al, 2015;Jeong et al, 2012;Krause et al, 2015;Strohmeier et al, 2013) made use of the technological progress in biogeochemical monitoring and increased the frequency and duration of measurements. High-frequency monitoring indeed has clear benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Jeong et al (2012) compared the response of DOC and particulate organic carbon (POC) in a forested headwater catchment in South Korea under various hydrologic conditions and found that POC was largely exported at high flow, while DOC is mainly exported at low flow. Grayson and Holden (2012) investigated the behavior of DOC in a bog system in northern Englandfocusing on the absorbance at different wavelengths to characterize the specific composition of DOC. Another study on 20 high-frequency DOC behavior was done by Strohmeier et al (2013) in a small forested catchment in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Grayson and Holden (2012) previously explored the use of an in-situ UV-Vis spectrophotometer to measure absorbance across the UV-Vis spectrum within a UK peatland stream. However, their study was focussed on the response of absorbance to flow conditions and did not include a DOC calibration.…”
Section: Introductionmentioning
confidence: 99%